The Effectiveness of Monetary Transmission Through Interest Rate and Exchange Rate Channels on Indonesia's Inflation Rate - Setyawan, Anggie Bayu; Wasiaturrahma, Wasiaturrahma; Anwar, Anas Iswanto (Jurnal Ilmu Ekonomi Terapan, 2023)
The purpose of this research is to determine the effectiveness of monetary transmission on inflation in Indonesia through the interest rate and the exchange rate channel over a period of 2015Q1-2022Q4. This research analysis approach uses the variance decomposition and Vector Error Correction Model (VECM) methods. Quantitative methods are utilized, and the estimation tool used is Eviews 12. The findings of the variance decomposition analysis in this research indicate that to reduce inflation in Indonesia, monetary transmission through exchange rates is more effective than through the interest rate channel.